2016
DOI: 10.1080/10669817.2015.1106818
|View full text |Cite
|
Sign up to set email alerts
|

The symptomatic and functional effects of manual physical therapy on plantar heel pain: a systematic review

Abstract: Objectives: Plantar heel pain is common and can be severely disabling. Unfortunately, a gap in the literature exists regarding the optimal intervention for this painful condition. Consequently, a systematic review of the current literature regarding manual therapy for the treatment of plantar heel pain was performed. Methods: A computer-assisted literature search for randomized controlled trials in MEDLINE, EMBASE, Cochrane, CINAHL, and Rehabilitation & Sports Medicine Source, was concluded on 7 January 2014. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 39 publications
(65 reference statements)
0
23
0
2
Order By: Relevance
“…All participants received up to eight treatment sessions at a frequency of once or twice per week over a 4-week period. Both groups received an impairment-based manual therapy approach directed to the lower limb,[ 6 , 13 , 26 , 28 , 58 ] an exercise program[ 7 , 12 , 13 , 29 , 42 , 43 ] including self-stretching of the plantar fascia and the Achilles tendon and strengthening exercises for the intrinsic muscles of the foot, and therapeutic ultrasound[ 6 , 30 , 50 ] (Sonicator, Mettler Electronics, Anaheim, CA; 3 MHz, 1.5 W/cm 2 , 20% duty cycle for 5 minutes to the most tender region of the proximal portion of the plantar fascia). Details regarding the manual therapies and exercise program are provided in S2 Table .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All participants received up to eight treatment sessions at a frequency of once or twice per week over a 4-week period. Both groups received an impairment-based manual therapy approach directed to the lower limb,[ 6 , 13 , 26 , 28 , 58 ] an exercise program[ 7 , 12 , 13 , 29 , 42 , 43 ] including self-stretching of the plantar fascia and the Achilles tendon and strengthening exercises for the intrinsic muscles of the foot, and therapeutic ultrasound[ 6 , 30 , 50 ] (Sonicator, Mettler Electronics, Anaheim, CA; 3 MHz, 1.5 W/cm 2 , 20% duty cycle for 5 minutes to the most tender region of the proximal portion of the plantar fascia). Details regarding the manual therapies and exercise program are provided in S2 Table .…”
Section: Methodsmentioning
confidence: 99%
“…frequency, intensity, duration) of manual therapy remains unclear. [ 28 ] Strength training of the intrinsic foot musculature may be effective for improving pain and function in PF. [ 29 ] Although the APTA clinical practice guidelines do not recommend ultrasound therapy for PF,[ 22 ] a recent systematic review concluded that “the available higher-quality evidence suggests that patients with persistant PF may benefit from therapeutic ultrasound.”[ 30 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when defining the scope of the CCS, we ultimately chose to restrict its content and recommendations to primarily those aspects that most foot and ankle surgeons have direct control over. Several excellent reviews have been reported on the topic of physical therapy and plantar fasciitis, and we would refer interested readers to the original sources for more information (5,6).…”
mentioning
confidence: 99%